Peluang Pasar Pada Tourism Metaverse Di Dki Jakarta - rizki Nugraha; Arsya Ananda (Jurnal Ilmiah Wahana Pendidikan, 2023)
Metaverse is a combination of two words namely "meta" and "universe" which describes a relationship or connection that goes beyond normal boundaries using internet technology. Currently digital media has a very broad and promising market opportunity because it can be easily accessed with a wide range as well, by making use of facilities such as social media, and so on, Metaverse in Indonesia itself is still in the development stage and will go through several stages of development. Tourism is a travel activity from one place to another with a temporary period of time. This study uses a literature study method with the aim of obtaining an overviewof the Metaverse market opportunity in DKI Jakarta. This study uses secondary data whose data comes from literature studies and document studies on the Metaverse from previous articles. This study uses data collection techniques with library research